A STUDY ON AWARENESS OF READING STRATEGIES OF THE THIRD SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Bastian, Heri; Delfi, Syofia; M. Syarfi, M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: this descriptive research is aimed to find out the awareness of reading strategies of the third semester students of English Study Program FKIP Universitas Riau. The sample of this research is one of three classes of the second year students of English Study Program which were chosen by using cluster random sampling technique. The number of sample is 37 students. The data were collected by giving a set of questionnaire to the students individually. The questionnaire is about Survey of Reading Strategies (SORS) with 3 indicators is Global Reading Strategies (GLOB), Problem Solving Strategies (PROB), and Support Strategies (SUP). The students score were analyzed by using the frequency and percentages of each item. The results were divided into 3 categories. Then, the range of each category is found by using the formula as stated by Gay which is fall into 3 categories: high, moderate and lowest. The finding showed that more than half of the total number of the students have good ability in using a reading strategies. They are 26 students (70.27%) in moderate level. There are 9 students (24.32%) who are in high level and 2 students (5.40%) who are in low level. It can be concluded that the students’ ability in reading strategies is in good level. This study recommended the students to keep improve their ability, because there is no any limitation in developing the ability, so that it is better for the students to keep improved their ability.Key Words: Study, Ability, Reading, Strategies